Pattern of pediatric dermatoses in a tertiary hospital in South India - Panchatsharam, Adithyan; Sundaramurthy, Revathy (International Journal of Research in Dermatology, 2023)
Background: Several cross-sectional studies in the form of school surveys and studies on paediatric patients visiting dermatology OPD in tertiary care hospital has been conducted in the last three decades. This study was conducted to note the pattern of paediatric dermatoses and also to compare the difference in disease pattern with other studies conducted in southern India in last decade. Methods: A retrospective cross-sectional study was conducted at the Dermatology department of MVJ teaching hospital to determine the pattern of pediatric dermatoses from May 2021 to October 2021 after obtaining institutional ethics committee clearance. Cases under the age of 18 years were included in the study. Cases with age above 18 years, incomplete data, dermatoses where diagnosis was uncertain were excluded from the study. A total of 150 children were included in the study. The results were entered and tabulated in MS-excel sheet and descriptive analysis was done. Results: 150 children were included in the study.36 types of dermatoses were noted overall. Eczematous diseases (32.7%) contributed to the maximum followed by infections and infestations (25.3%). The most frequent dermatoses found were Atopic dermatoses (10%), pityriasis alba (8.6%), scabies (8.6%), Acne vulgaris (8.6%). Eczematous diseases and hypersensitivity disorders were noted to have increased frequency when compared to other studies in last one decade Conclusions: Rising trend in atopic dermatitis has been noted which might be due to changing environmental factors and also due to better recognition of condition by physicians in last one decade. With respect to spectrum of skin infections and infestations not much of difference is appreciated when compared to previous studies